Optimal Public Transportation Networks: Evidence from the World's Largest Bus Rapid Transit System in Jakarta - Gabriel Kreindler; Arya Gaduh; Tilman Graff; Rema Hanna; Benjamin A. Olken (American Economic Review, 2026)
Designing public transport networks involves trade-offs between coverage, service frequency, and direct service. We use the expansion of the bus system in Jakarta, Indonesia, to study these trade-offs. We analyze how new direct connections, changes in bus travel time, and wait-time reductions affect bus ridership and aggregate flows and estimate a transit network demand model by matching the route launch events. Commuters in Jakarta are 2–3 times more sensitive to wait time than bus time and inattentive to long routes. We develop a flexible framework to characterize optimal networks. A less concentrated network would increase ridership and commuter welfare. (JEL L92, L98, O18, R41, R42, R48)